Glacial isostatic adjustment in response to changing Late Holocene behaviour of ice streams on the Siple Coast, West Antarctica - Nield, GA; Whitehouse, PL; Matt King; Clarke, PJ (2016)
The Siple Coast region of Antarctica contains a number of fast-flowing ice streams, which control the dynamics and mass balance of the region. These ice streams are known to undergo stagnation and reactivation cycles, which lead to ice thickness changes that may be sufficient to excite a viscous solid Earth response (glacial isostatic adjustment; GIA). This study aims to quantify Siple Coast ice thickness changes during the last 2000 yr in order to determine the degree to which they might contribute to GIA and associated present-day bedrock uplift rates. This is important because accurate modelling of GIA is necessary to determine the rate of present-day ice-mass change from satellite gravimetry. Recently-published reconstructions of ice-stream variability were used to create a suite of kinematic models for the stagnation-related thickening of Kamb Ice Stream since ∼1850 AD, and a GIA model was used to predict present-day deformation rates in response to this thickening. A number of longer-term loading scenarios, which include the stagnation and reactivation of ice streams across the Siple Coast over the past 2000 yr, were also constructed, and used to investigate the longer term GIA signal in the region. Uplift rates for each of the ice loading histories, based on a range of earth models, were compared with regional GPS-observed uplift rates and an empirical GIA estimate. We estimate Kamb Ice Stream to have thickened by 70–130 m since stagnation ∼165 years ago. Modelled present-day vertical motion in response to this load increase peaks at −17 mm yr –1 (i.e. 17 mm yr –1 subsidence) for the weakest earth models tested here. Comparison of the solid Earth response to ice load changes throughout the last glacial cycle, including ice stream stagnation and reactivation across the Siple Coast during the last 2000 yr, with an empirical GIA estimate suggests that the upper mantle viscosity of the region is greater than 1 × 10 20 Pa s. When upper mantle viscosity values of 1 × 10 20 Pa s or smaller are combined with our ...